Microbial dormancy as an ecological and biogeochemical regulator on Earth - James A. Bradley (Nature Communications)
Abstract Virtually all of Earth’s ecosystems and biogeochemical cycles are underpinned – and often driven – by the activity (or inactivity) of microorganisms. Dormancy, a reversible state of reduced metabolic activity, is ubiquitous among microbial communities in environments ranging from moderate to extreme. Dormancy enables microorganisms to withstand severe and widespread environmental changes. Here I argue that dormancy exerts a powerful influence on Earth’s ecological and biogeochemical architecture through space and time, and over vast scales. Dormancy manifests differently across taxonomically and functionally distinct microbial groups, and operates over timescales ranging from hours to millennia – enabling microorganisms to interact with the geosphere over geologically relevant timescales. As such, dormancy may play a crucial role in shaping ecosystems and biogeochemical cycles throughout the Earth system. Interdisciplinary, integrative geosphere-biosphere approaches will be essential for advancing our understanding of how microbial dormancy underpins the co-evolution of Earth, its biosphere, and their interactions.